On the rejection of internal and external disturbances in a wind energy conversion system with direct-driven PMSG. (March 2016) - Li, Shengquan; Zhang, Kezhao; Li, Juan; Liu, Chao
Abstract: This paper deals with the critical issue in a wind energy conversion system (WECS) based on a direct-driven permanent magnet synchronous generator (PMSG): the rejection of lumped disturbance, including the system uncertainties in the internal dynamics and unknown external forces. To simultaneously track the motor speed in real time and capture the maximum power, a maximum power point tracking strategy is proposed based on active disturbance rejection control (ADRC) theory. In real application, system inertia, drive torque and some other parameters change in a wide range with the variations of disturbances and wind speeds, which substantially degrade the performance of WECS. The ADRC design must incorporate the available model information into an extended state observer (ESO) to compensate the lumped disturbance efficiently. Based on this principle, a model-compensation ADRC is proposed in this paper. Simulation study is conducted to evaluate the performance of the proposed control strategy. It is shown that the effect of lumped disturbance is compensated in a more effective way compared with the traditional ADRC approach. Highlights: Consider the WECS driven by PMSG with internal and external disturbances. A maximum power point tracking strategy based on ADRC scheme is given. A model-compensation ADRC is proposed to address the rapid change of disturbances. The proposed ADRC is employed to improve the performance of PMSG based WECS.